(untitled) (Confluenţe Bibliologice, 2025)
Calimah, a notable librarian of the 3rd century BC, was responsible for the administration of the Library of Alexandria, where he introduced an advanced cataloging system, recognized as the first alphabetical catalog of literary and scientific works, the foundation for the development of the modern library.